A rare case of postpartum paraplegia: A case report - Dinesh Kumar; Gursimran Kaur; Suhaavi Kaur Chawla; Harroop Singh (Wolters Kluwer Medknow Publications, 2024)
In this case report, a 27-year-old woman who had pre-eclampsia in the past and had a cesarean section as a result of the condition presents with an uncommon and difficult form of postpartum paraplegia. She experienced bilateral lower limb paralysis and urine incontinence soon after the surgery, which quickly led to unconsciousness and required mechanical ventilator support and intensive care treatment. Comprehensive diagnostic testing, which included magnetic resonance imaging scans of the brain and spinal cord, identified signs typical of "Posterior Reversible Encephalopathy Syndrome (PRES)" and spinal cord infarction affecting segments C3 to D2. "Antiphospholipid Antibody Syndrome (APLA)" was identified by laboratory testing, highlighting the significance of taking a thorough approach to comprehending this uncommon clinical condition. Treatment included anticoagulant therapy, high-dose steroid therapy, and antihypertensive drugs, emphasizing the crucial importance of inter-disciplinary care in handling such complex situations. Even if the patient's symptoms have partially improved, their condition is still being closely monitored in the intensive care unit. In the context of postpartum neurological problems and the complex interplay between pre-eclampsia, spinal cord infarction, and related clinical symptoms, this case emphasizes the need for increased awareness and prompt management.